RRM2 Mediates the Anti-Tumor Effect of the Natural Product Pectolinarigenin on Glioblastoma Through Promoting CDK1 Protein Degradation by Increasing Autophagic Flux - Jiang, Haiping; Zhang, Dongzhi; Aleksandrovich, Karpov Denis; Ye, Junyi; Wang, Lixiang; Chen, Xiaofeng; Gao, Ming; Wang, Xinzhuang; Yan, Tao; Yang, He; Lu, Enzhou; Liu, Wenwu; et al. (Frontiers in Oncology, 2022)
The natural product pectolinarigenin exerts anti-inflammatory activity and anti-tumor effects, and exhibits different biological functions, particularly in autophagy and cell cycle regulation. However, the antineoplastic effect of pectolinarigenin on glioblastoma (GBM) remains unclear. In the present study, we found that pectolinarigenin inhibits glioblastoma proliferation, increases autophagic flux, and induces cell cycle arrest by inhibiting ribonucleotide reductase subunit M2 (RRM2), which can be reversed by RRM2 overexpression plasmid. Additionally, pectolinarigenin promoted RRM2 protein degradation via autolysosome-dependent pathway by increasing autophagic flow. RRM2 knockdown promoted the degradation of CDK1 protein through autolysosome-dependent pathway by increasing autophagic flow, thereby inhibiting the proliferation of glioblastoma by inducing G2/M phase cell cycle arrest. Clinical data analysis revealed that RRM2 expression in glioma patients was inversely correlated with the overall survival. Collectively, pectolinarigenin promoted the degradation of CDK1 protein dependent on autolysosomal pathway through increasing autophagic by inhibiting RRM2, thereby inhibiting the proliferation of glioblastoma cells by inducing G2/M phase cell cycle arrest, and RRM2 may be a potential therapeutic target and a prognosis and predictive biomarker in GBM patients.